Gut mycobiota alterations in patients with COVID-19 and H1N1 infections and their associations with clinical features - Longxian Lv (Nature Portfolio, 2021)
Lv et al. associate the gut mycobiota with clinical features and the bacterial microbiota by comparing COVID-19 patients to those infected with H1N1 and healthy controls. They find that gut mycobiota dysbiosis occurs in both COVID-19 patients and those infected with H1N1 and that it does not improve until patients no longer require medical attention, providing insights into a better healthcare guideline.